Korelasi Jabatan Fungsional, Kepangkatan, Masa Kerja, Ijasah Dengan Profesionalitas Dosen Jurusan Tarbiyah Sekolah Tinggi Agama Islam Negeri (STAIN) Kediri - Ali Anwar (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
The present study aims at examining teacherâ€™s professionalism and its reciprocal relation with functionalÂ position, rank stratification, length of work, and the diploma. Besides intended to verify the theory of JamesÂ H. Stronge et al, this study can also be employed to evaluate Peraturan Pemerintah RI number 37 year 2009Â Chapter 7, that states that teacher certification is valid as long as the teachers conduct their assignment asÂ teachers, and it is not necessarily evaluated regularly.Â Data collection technique in the present study was executed through documentation and questionnaire. The Â total of the student sample who provided their assessment on the teacher professionalism was 328, with 8Â students representing each class. Each student provides their assessment for all teachers who were teaching inÂ even semester of 2013-2014. Kendali tau was then employed for the data analysis technique.Â This study concluded that, firsly, functional position is negatively correlated with teacher professionalism at theÂ Department of Tarbiyah STAIN Kediri; secondly, rank stratification is also negatively correlated with teacherÂ professionalism; thirdly, length of teaching is not correlated with teacher professionalism; and fourthly, level ofÂ diploma is also not correlated with teacher professionalism at the Department of Tarbiyah STAIN Kediri.